2015
DOI: 10.1155/2015/214021
|View full text |Cite
|
Sign up to set email alerts
|

Educational Effectiveness, Target, and Content for Prudent Antibiotic Use

Abstract: Widespread antimicrobial use and concomitant resistance have led to a significant threat to public health. Because inappropriate use and overuse of antibiotics based on insufficient knowledge are one of the major drivers of antibiotic resistance, education about prudent antibiotic use aimed at both the prescribers and the public is important. This review investigates recent studies on the effect of interventions for promoting prudent antibiotics prescribing. Up to now, most educational efforts have been target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
99
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 103 publications
1
99
0
5
Order By: Relevance
“…and/or level of exposure to AMS in educational institutions, in the various study areas. Thus, the finding of very low proportion of respondents that have heard of ABS in this study, suggested there is little or no AMS education awareness (via mass media, in schools, social centres, etc) in the study area (Abbo et al, 2013;Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…and/or level of exposure to AMS in educational institutions, in the various study areas. Thus, the finding of very low proportion of respondents that have heard of ABS in this study, suggested there is little or no AMS education awareness (via mass media, in schools, social centres, etc) in the study area (Abbo et al, 2013;Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…It equally suggested that there is no ASP in form of continuing education, conferences, seminars, symposia, etc. (Lee et al, 2015) organized for veterinarians in the study area. It also suggested that curricula in Nigerian Veterinary schools are deficient on issues of ABR and ABS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very recent review article mentioned similarly that to promote prudent antibiotic prescribing the best time of intervention is during undergraduate medical studies. 16 Regarding the source of antimicrobial information, nearly half of current study respondents were uncertain about the presence of hospital guidelines. This was because the MS were not allowed to prescribe for the patients during their study periods in Bangladesh.…”
Section: Discussionmentioning
confidence: 97%